A note on stability of Hardy inequalities - Suragan, Durvudkhan; Ruzhansky, Michael; Ruzhansky, Michael (Springer Science and Business Media LLC, 2018)
In this note, stability versions of the Hardy inequalities are formulated within the framework of Folland and Stein’s homogeneous groups. This yields new remainder estimates for Rellich-type inequalities in that setting. Unlike classical Euclidean results, these stability estimates hold for arbitrary homogeneous quasi‑norms.
Keywords: In this note, stability versions of the Hardy inequalities are formulated within the framework of Folland and Stein’s homogeneous groups. This yields new remainder estimates for Rellich-type inequalities in that setting. Unlike classical Euclidean results, these stability estimates hold for arbitrary homogeneous quasi‑norms.